Manusia Dalam Prespektif Psikologi Pendidikan Islam - Rahmi, Novita (Jurnal Dewantara, 2016)
Psychology of Islam can be concluded as the science which deals with psychiatric based on the source qanunu Islam (Qur'aan and Sunnah nabawiyah). Thus the Islamic Educational Psychology is a science of applied psychology in the education system that is based on Quran and Hadith. By putting Islamic psychology of human scientific effort to understand the verses and passages qauliyah kauniyah working in man, then at a certain level of thinking distance between Psychology with Islam not as far as imaginable. Al-Quran and al-Hadith loaded with righteous laws about psychology, and instead examine the psychology of many supporting the truth. Thus opened crevices relationship between the two. Religion offers principles, foundation, and referrals for psychological trap methodology provides scientific explanations for religion.